(untitled) (American Journal of Islam and Society, 2020)
To scholars of the Nahda, that is, the Arab cultural renaissance which unfolded in Egypt and Ottoman Syria over the course of the late nineteenth and early twentieth centuries, the journalist, teacher, and writer Buṭrus al-Bustānī is well familiar. However, few might be aware that al-Bustānī was also a committed Protestant Christian involved in building local church structures. Probably even fewer know that his daughter, Alice al-Bustānī, and other members of his extended family were at once important figures within the Syrian Protestant church and central protagonists of the Nahda. To read the full book review, download the PDF file on the right.